The Lost Girl - Lawrence, D. H. (David Herbert), 1885-1930 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Lost Girl" by D. H. Lawrence is a novel written in the early 20th century. The story is set in the small industrial town of Woodhouse in England and revolves around Alvina Houghton, the daughter of a struggling merchant, as she grapples with societal expectations and her identity. As the narrative unfolds, it delves into themes of women, individuality, and the constraints of society. At the start of the book, we are introduced to the declining fortunes of Alvina$1 (Bs father, James Houghton, who once dreamed of becoming a successful merchant but now faces financial hardships. The narrative provides an insightful portrait of the family's dynamics, particularly focusing on the influences of Alvina's mother, an invalid, and her governess, Miss Frost. As Alvina grows into a young woman, she finds herself overshadowed by her father's failures and the societal pressures surrounding her, hinting at her struggle against the expectations of becoming another "old maid" in a society filled with unmarried women. The opening sets a tone that promises a deep exploration of Alvina's journey towards self-discovery and independence. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Lost_Girl
Release date is 2007-12-03
Roger Frank, Roberta Staehlin, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Psychological fiction; Young women -- Fiction; Love stories; Midlands (England) -- Fiction; Circus performers -- Fiction; Naples (Italy) -- Fiction